Al-Zahrawi's explaination on bone fractures and its surgical and non-surgical treatments - Zulkifli, Nur Izzati; Othman, Raihan (IIUM Press, 2011)
The main focus in this work is to highlight the detail knowledge concerning bone fractures and its treatments as explained by AI-Zahrawi from his observations and experiences. The significance of this chapter consists of descriptions in orthopaedic diagnosis and treatment by Al Zahrawi. The methodology adopted in this study is library based research and all evidences were collected from reliable sources. Abu AI-Qasim AIZahrawi practised medicine and surgery in Cordova. He was also born in Zahra, the neighbourhood of Cordova. His famous book AI-Tasrif, a medical encyclopaedia covering 30 volumes which included sections on surgery, medicine, orthopaedics, ophthalmology, pharmacology, nutrition etc, was the greatest explaination on medicine